THE IMPACT OF COVID-19 ON COMPETITIVENESS OF AGRI-FOOD PRODUCTIS FROM THE REPUBLIC OF MOLDOVA - Artur GOLBAN; Rita GOLBAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The World Economy was stricken by COVID-19 virus in 2020, which influenced negatively the economic processes determining the decreasing of the global productivity of labour, the decreasing of the productivity of agricultural products and at the end the decreasing of the competitiveness of states all over the World. In this scientific research is analysed the impact of COVID-19 on competitiveness of agri-food products from the Republic of Moldova, the problems regarding the exports of agri-food products, the markets of agri-food products and are proposed measures to get out from the crisis situation determined by the COVID-19.